Bactericidal effectiveness of the developed disinfectant "RabbitDez" in the production conditions of a rabbit farm - Romazan, I.; Turko, I. (Scientific Progress & Innovations, 2024)
When developing a new biocide, "RabbitDez," for aerosol disinfection of premises, its effect on the microbiota of the fur and nasal passages of rabbits, as well as on the microflora of the air of rabbit hutches and environmental objects, was established, which was the purpose of the work. To study the bactericidal activity of the disinfectant, three groups of 28 rabbits each were formed: the control group, the first and second experimental groups were formed by animals that were subjected to 30 min of aerosol treatment with 2 % solutions of the disinfectant "RabbitDez," and the prototype "Zoodizin," respectively. 2 h after disinfection, the number of microorganisms was determined in the washes from the fur, nasal passages of animals and from the surfaces of the floor of cages, feeders, walls and windows, as well as in the air of rabbit hutches. As a result of the studies, it was found that the frequency of detection of Bacillus spp. from rabbit fur decreased by 71.5 % when using the disinfectant "RabiDez" and by 64.3 % when treated with the disinfectant "Zoodizin" and Candida spp. by 66.6 % and 58.4 %, respectively. At the same time, no cases of total coliforms identification were observed. When using the "RabiDez" and "Zoodizin" disinfectants, the quantitative Bacillus spp. decreased by 42.6 % and 39.1 %, Candida spp. by 46.4 % and 40.6 %, MAFAnM by 57.0 % and 56.0 % respectively. At the same time, both biocides showed a 100 % bactericidal effect on total coliforms. The frequency of isolation of Staphylococcus spp. from the nasal passages decreased by 50.1 % under the action of the biocide "RabiDez" and by 46.1 % under the influence of the prototype "Zoodizin," Bacillus spp. by 80.8 % and 76.9 %, total coliforms by 100 %, Candida spp. by 65.4 % and 57.6 % respectively. Quantitatively, the level of Staphylococcus spp. decreased under the action of the product "RabitDez" by 48.3 % and under the action of the prototype "Zoodizin" by 41.2 %, respectively Bacillus spp. by 52.4 %, and 39.3 %, Candida spp. by 58.3 % and 46.0 %, total coliforms by 100 %, and MAFAnM by 59.6 % and 53.1 %. The use of the disinfectant "RabitDez" and the prototype "Zoodizin" provides a 99% bactericidal effect on Candida spp., Staphylococcus spp., and MAFAnM, which were on the floor of the cages, feeders, walls, and windows, and in the air of the room where the rabbits were kept.